1984
DOI: 10.1210/endo-114-1-305
|View full text |Cite
|
Sign up to set email alerts
|

l-THYROXINE AND 3,5,3’-TRII000-l-THYRONINE IN RAT EMBRYOS BEFORE ONSET OF FETAL THYROID FUNCTION.

Abstract: T4 and T3 have been measured by RIA in 10-12-day-old rat embryo-trophoblasts, and in 13-20-day-old embryos and placentas, as well as in a few samples of amniotic fluid. Both T4 and T3 were measured after extraction of the samples with ethanol, purification by paper chromatography, anion exchange resin, or both. T4 and T3 could be shown in all samples studied. The amounts of T4 and T3 per conceptus and their concentrations were higher in embryo-trophoblasts and placentas than in 13-18-day-old embryos. The conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
82
0
2

Year Published

1986
1986
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(90 citation statements)
references
References 0 publications
6
82
0
2
Order By: Relevance
“…Both T 4 and T 3 have been detected in rat embryo (20) and fetal rat brain (21) before the onset of fetal thyroid function. Morreale de Escobar et al (22) demonstrated that maternal hypothyroxinemia due to iodine deficiency resulted in lack of thyroid hormone in fetal tissues during early pregnancy, even before the onset of fetal thyroid function.…”
Section: Discussionmentioning
confidence: 99%
“…Both T 4 and T 3 have been detected in rat embryo (20) and fetal rat brain (21) before the onset of fetal thyroid function. Morreale de Escobar et al (22) demonstrated that maternal hypothyroxinemia due to iodine deficiency resulted in lack of thyroid hormone in fetal tissues during early pregnancy, even before the onset of fetal thyroid function.…”
Section: Discussionmentioning
confidence: 99%
“…In humans as well as in rodents, thyroid hormones as well as their receptors are present in the fetus prior to the onset of fetal thyroid hormone A c c e p t e d M a n u s c r i p t production underscoring the relevance of maternal thyroid hormone production for fetal development (Bernal and Pekonen, 1984;Obregón et al, 1984;Contempré et al, 1993;Morreale de Escobar et al, 2004). For instance, already at week 12 of gestation both T4 and T3 can be detected in the human developing cortex but not in the serum and other fetal tissues.…”
Section: Ontogenesis Of Thyroid Hormone Actionmentioning
confidence: 99%
“…However, microglial cells were already present in the developing rat brain at E12 (Ashwell, 1991;Sorokin et al, 1992), 4 d before the beginning of MTU treatment (E16). Early transplacental transfer of thyroid hormones from the mother (Obregon et al, 1984;Porterfield and Hendrich, 1992) therefore might have influenced the early fetal development of the microglial cells.…”
Section: Thyroid Hormone Favors Microglia Expansion: Early Postnatal mentioning
confidence: 99%